2018
DOI: 10.5380/avs.v23i1.50585
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of behavior and feeding intake of dogs fed with soybean hulls

Abstract: The diet composition can promote satiety and interfere in animal behavior. The aim of this study was to evaluate the behavior of dogs after ingestion of diet without soybean hull (0%SH) and a diet with soybean hulls (16%SH), as well as the daily consumption of food (supplied-leftovers) and metabolizable energy (ME) intake of diets. Twelve Beagle dogs were distributed completely randomly between two treatments, being six dogs consuming the 0%SH diet and six dogs 16%SH diet. The behavioral test consisted of obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…There were no differences in the dogs’ behavior with dietary soybean hull inclusion. Similarly, Scheraiber et al (2018) evaluated dog behavior after eating diets with or without soybean hulls (0 or 16%) [ 45 ]. They observed a reduction in scratching behavior and stereotypical behavior (repetitive regular movements) ( p < 0.10) in animals fed a diet containing soybean hulls [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no differences in the dogs’ behavior with dietary soybean hull inclusion. Similarly, Scheraiber et al (2018) evaluated dog behavior after eating diets with or without soybean hulls (0 or 16%) [ 45 ]. They observed a reduction in scratching behavior and stereotypical behavior (repetitive regular movements) ( p < 0.10) in animals fed a diet containing soybean hulls [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Dietary soybean hulls decreased the deposition of subcutaneous lipids in dogs [ 38 ], providing further evidence that soybean ingredients could benefit animal health. Studies on dog behavior in response to dietary soybean hull inclusion showed either no difference or a reduction in scratching behavior with a lower metabolizable energy intake when soybean hulls were present in the diet [ 33 , 45 ]. Numerous studies in the literature have shown that dietary soybean ingredients increase fermentative products by the hindgut microbiome and can result in a healthy gut by acting as prebiotics in companion animals.…”
Section: Discussionmentioning
confidence: 99%